KEKUATAN ALAT BUKTI SURAT (VISUM ET REPERTUM) DALAM PEMBUKTIAN DAKWAAN PERSETUBUHAN ANAK - Lathifah Nur Azizah; Bambang Santoso (Verstek, 2023)
This study aims to determine the urgency ofVisum et Repertumin proving the crime of child intercourse and to find out the judge's consideration of documentary evidence (Visum et Repertum) in deciding cases of child intercourse. This research is normative or doctrinal legal research with a case approach. The types of data used are primary and secondary data. The technique used in collecting legal materials for this research is document or literature study. This study uses the analysis technique of the syllogism method which is deductive in nature, namely by using the major premise in the form of legal rules and proceeding to the minor premise in the form of legal facts. From these two premises, a conclusion is drawn. Based on this research, the results obtained were that in proving the indictment of the crime of child sexual intercourse, the Decision of the Surakarta District Court Number 4/Pid.Sus-Anak/2021/PN. SktVisum et Repertumhas an important role because the crime of intercourse is carried out in a quiet place so it will be difficult to find witnesses who can see or hear. Apart from that, in child intercourse, the child's immature condition makes it difficult for the child to reveal what has happened to him. Therefore, the evidence found on the victim's body has an important role.Keywords: Child intercourse, Visum et Repertum, Evidence